Hydrocarbon compositions and physicochemical characteristics for the determination of gasoline quality: An implication from gas chromatographic fingerprints. Issue 15 (3rd August 2017) - Naggar, A. Y. El; Elkhateeb, A.; Altalhi, T. A.; El Nady, Mohamed M.; Alhadhrami, A.; Ebiad, M. A.; Salem, A. A.; Elhardallou, S. B.
ABSTRACT: Two gasoline samples were collected from Saudi Arabia petrol station and subjected for studying their quality as liquid fuel. Gasoline samples were characterized and compared by studying their physicochemical properties such as average molecular weight, relative density, percent carbon, percent hydrogen, total oxygen content, and octane number. In addition, it was performed to study the group analysis and detailed hydrocarbon composition of automotive gasoline samples via gas chromatographic (GC) fingerprints as a practical method for quality detection.